Nonlinear Damped Vibrations of a Laminated Composite Plate Subject to Blast Load - Kazanci, Zafer; Mecitoglu, Zahit (American Institute of Aeronautics and Astronautics (AIAA), 2005)
This research deals with the derivation and solution of nonlinear dynamic equations of a clamped laminated plate exposed to blast load including structural damping effects. Dynamic equations of the plate are derived by the use of the virtual work principle. The geometric nonlinearity effects are taken into account with the von Karman large deflection theory of thin plates. An appropriate approximate solution is assumed for the space domain considering the finite element analysis results for the large deformation static analysis of the laminated plate. The Galerkin method is used to obtain the nonlinear differential equations in the time domain. These nonlinear differential equations include structural damping effects. The finite difference method is applied to solve the system of coupled nonlinear equations. The results of the theoretical analysis are compared with the experimental results. Good agreement is found for the peak values and frequencies. Effects of aspect ratio and damping on the dynamic response of the plate are examined. The damping coefficient greatly affects the nonlinear dynamic response.